Introducing “Journeys Home” - Watson, N; Bevitt, A; Killackey, E; Moschion, J; Johnson, G; Scutella, R; Greer, N; Tseng, Y; Wooden, M; Chigavazira, A (My University, 2013)
Homelessness, despite being a major social policy issue in Australia, is an area that is not well served by data. Most sorely lacking is any large-scale panel study that follows a broad sample of persons with recent experience of homelessness and unstable housing histories. In 2010, the Australian Government set about rectifying this deficiency when it commissioned the Melbourne Institute to undertake a new panel study, now known as ‘Journeys Home’. This study draws its sample from the population of Centrelink income-support recipients, targeting persons identified in the administrative data as having recent experience of homelessness, as well as others with similar characteristics who may be vulnerable to housing difficulties in the future. This article summarises the design of this new study and reports on fieldwork outcomes from the first two waves of data collection.
The Australian Economic Review
Keywords: Surveys and Survey Methodology -- Fieldwork; Surveys and Survey Methodology; Surveys and survey methodology; Surveys and Survey Methodology; Fieldwork; Surveys and Survey Methodology